Physiology of pericardial fluid production and drainage - Vogiatzidis, Konstantinos; Zarogiannis, Sotirios G.; Aidonidis, Isaac; Solenov, Evgeniy I.; Molyvdas, Paschalis-Adam; Gourgoulianis, Konstantinos I.; Hatzoglou, Chrissi (Frontiers in Physiology, 2015)
The pericardium is one of the serosal cavities of the mammals. It consists of two anatomical structures closely connected, an external sac of fibrous connective tissue, that is called fibrous pericardium and an internal that is called serous pericardium and coats the internal surface of the fibrous pericardium (parietal layer) and the heart (visceral layer) forming the pericardial space. Between these two layers a small amount of fluid exists that is called pericardial fluid. The pericardial fluid is a product of ultrafiltration and is considered to be drained by lymphatic capillary bed mainly. Under normal conditions it provides lubrication during heart beating while the mesothelial cells that line the membrane may also have a role in the absorption of the pericardial fluid along with the pericardial lymphatics. Here we provide a review of the the current literature regarding the physiology of the pericardial space and the regulation of pericardial fluid turnover and highlight the areas that need to be further investigated.